Nonlinear Analysis of Multilayered Composite Plates Using Modified Finite Elements - أبو دياب سليمان; حويجة بسام; حسن ابراهيم (Latakia University Journal -Engineering Sciences Series, 2022)
In this study, multilayered composite plates will be analyzed (Plates which consists of many layers with one or more materials ) using multilayered modified finite element displacement approach in the nonlinear case (Large displacements , small rotations). Using incremental iterative approach, stiffness matrix, external equivalent loading vector and new terms resulting from the application of the modified finite element approach will be concluded. This study uses a Matlab code for the analysis of composite plates, some examples will be computed and plotted. The results of the displacements, stresses, strains and internal forces will be computed and plotted for a number of homogeneous isotropic or orthotropic multilayered composite plates. Finally results will be compared in order to check the validity of our method.